Maternal and neonatal outcomes and determinants of iodine deficiency in third trimester of pregnancy in an iodine sufficient area - Soraya Saleh Gargari; Reyhaneh Fateh; Mina Bakhshali-bakhtiari; Masoumeh Saleh; Masoumeh Mirzamoradi; Mahmood Bakhtiyari (BMC, 2020)
Abstract Background Mild to moderate iodine deficiency in pregnant women may expose them to the increased risk of the development of goiter and thyroid disorder. There is a relationship between low maternal UIC (Urinary iodine concentration) in pregnancy and diminished placental weight and neonatal head circumference. The current study was an attempt to assess iodine nutritional status, its determinants and relationship with maternal and neonatal outcomes. Methods In this population based cross-sectional study, which was conducted from April 2017 to September 2018, information was collected from 884 women of 20-45 years old who referred for periodic pregnancy visits. UIC was measured in random urine samples by applying a manual method which was based on the Sandell-Kolthoff technique. Information related to neonatal and maternal complications was collected from the individuals enrolled in the study through systematic follow-ups of the research team in each hospitals and the referral of trained midwives to the place of delivery and the retrieval of the case files. Results The results showed that out of 884 participants 838 (94.8%) had a urinary iodine concentration of more than 150 micrograms/litre and 46 (5.2%) showed urinary iodine concentrations less than 150 micrograms/litre. The median (IQR) urinary iodine concentration in the third trimester was 176 (165-196) μg/l. According to the WHO criteria 46 of the participants (5.2%) had insufficient urinary iodine concentrations, 805 (91.06%) had adequate urinary iodine concentrations while 33 (3.73%) showed more than adequate levels. There were no participants with urinary iodine concentrations higher than 500 micrograms/litre. The main influencing factors on maternal iodine deficiency in this study were weight gain during pregnancy (Odds Ratio (OR) =0.88, 95% CI: 0.82-0.95), number of previous pregnancy (OR = 0.59, 95% CI: 0.39-0.89) the interval between the most recent pregnancies (OR = 0.78, 95% CI: 0.64-0.95), whether or not the pregnancy has been Planned (OR = 2.92, 95% CI: 1.29-6.58) and nutritional complement consumption (OR = 3.64, 95% CI: 1.44-9.1). The need for a neonatal intensive care unit (NICU) admission (OR = 4.64, 95% CI: 1.81-11.9) and preterm birth (OR = 3.29, 95% CI: 1.51-7.1) were significantly related with maternal iodine deficiency before delivery. Also there is no significant differences regarding the mean maternal urinary iodine concentration between the normal and different maternal complications groups (p = 0.47). Conclusion Iodine deficiency in pregnant women can be improved by appreciate planning for pregnancy, proper inter-pregnancy time interval (> 12 months to < 5 years), appropriate nutrition during pregnancy. Besides, controlling maternal urinary iodine concentrations is important to prevent neonatal complications such as preterm delivery and NICU admission.